A green band in a parched and burning land: Sobaipuri O'odham landscapes - Seymour, Deni J., author; University Press of Colorado, publisher (Colorado State University. Libraries, 2022)
A Green Band in a Parched and Burning Land presents a detailed understanding of the Sobaipuri O'odham -- the most influential Indigenous group in southern Arizona in the early historic period. Seymour combines historical sources with archaeological data and oral history to reveal the native history of the region.--Provided by publisher.
Those Who Sing of the Green Band -- The Sobaipuri Landscape -- Documentary Clarification of the Gila River Sobaipuri Pima in Kino's Time -- Ethnogeographic Evaluation of the Great Principal Settlement of San Xavier del Bac -- Ópata or O'odham: The San Pedro Headwaters, Huachuca, and Babocomari -- Sobaipuri Settlement along Sonoita Creek -- San Pablo de Quiburi: The Sobaipuri O'odham Ranchería of Kino's Conception -- The Waning Days of Quiburi in 1780 -- Evaluating Di Peso's 1757 Jesuit Mission -- The Lower San Pedro: Tres Alamos to the Confluence -- New Understandings in Sobaipuri Research.
Keywords: Sobaipuri Indians -- Arizona -- History; Sobaipuri Indians -- Arizona -- Antiquities; Land settlement patterns -- Arizona -- History; Excavations (Archaeology) -- Arizona; Arizona -- Antiquities